2020
DOI: 10.3892/mmr.2020.10991
|View full text |Cite
|
Sign up to set email alerts
|

TNF‑α‑mediated epithelial‑to‑mesenchymal transition regulates expression of immune checkpoint molecules in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (Hcc) is the fastest growing cause of cancer-related deaths globally. epithelial-to-mesenchymal transition (eMT) is a cellular process that confers Hcc tumor cells with the ability to evade the immune system. immune escape in most tumors, including Hcc, is controlled by immune checkpoint molecules. The aim of the present study was to investigate the association between eMT and immune checkpoint in Hcc, and identify novel therapeutic targets for Hcc. an in vitro model of reversible eMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 56 publications
(57 reference statements)
0
39
0
Order By: Relevance
“…Another example of tumor-intrinsic immune escape described in HCC involves epithelial-to-mesenchymal-transition (EMT). A study by Shrestha et al investigated the association between EMT and induction of immune checkpoint expression in HCC ( 35 ). TNFalpha induced EMT in Hep3B and PLC/PRF/5 cells and led to the upregulation of PD-L1, PD-L2, CD73, and B7-H3, whereas reversal of EMT (MET) led to suppression of these markers ( 35 ).…”
Section: Tumor-intrinsic Mechanisms Of Immune Escape: Other Examples In Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of tumor-intrinsic immune escape described in HCC involves epithelial-to-mesenchymal-transition (EMT). A study by Shrestha et al investigated the association between EMT and induction of immune checkpoint expression in HCC ( 35 ). TNFalpha induced EMT in Hep3B and PLC/PRF/5 cells and led to the upregulation of PD-L1, PD-L2, CD73, and B7-H3, whereas reversal of EMT (MET) led to suppression of these markers ( 35 ).…”
Section: Tumor-intrinsic Mechanisms Of Immune Escape: Other Examples In Liver Cancermentioning
confidence: 99%
“…A study by Shrestha et al investigated the association between EMT and induction of immune checkpoint expression in HCC ( 35 ). TNFalpha induced EMT in Hep3B and PLC/PRF/5 cells and led to the upregulation of PD-L1, PD-L2, CD73, and B7-H3, whereas reversal of EMT (MET) led to suppression of these markers ( 35 ). In a cohort of 422 HCC patients, they demonstrated that high expression of TNFalpha and PD-L1 is associated with poor overall survival and expression of TNFalpha and PD-L2 was associated with increased HCC recurrence ( 35 ).…”
Section: Tumor-intrinsic Mechanisms Of Immune Escape: Other Examples In Liver Cancermentioning
confidence: 99%
“…Additionally, it has been observed that HIF-1 binds the NT5E gene promoter, confirming that hypoxia is a strong regulator of immune checkpoints dependent on ADO [ 20 ]. In a model of induction and reversion of EMT in hepatocellular carcinoma, TNF-〈 induced overexpression of the NT5E gene and reversion of EMT downregulation [ 176 ]. In agreement, a bioinformatics analysis using the gene Signature Finder Algorithm (gSFA) found in colorectal cancer that NT5E belongs to the gene signature of this disease, and that it is a transcriptional target of TNF-〈 [ 177 ].…”
Section: Purinergic Signaling and Cancer Hallmarksmentioning
confidence: 99%
“…In recent years, EMT has been closely associated with expression and regulation of immune checkpoint molecules in several cancers including lung cancer [18][19][20][21][22], breast cancer [23][24][25][26], oesophageal cancer [27], gastric cancer [27][28][29], salivary adenoid cystic carcinoma [30], pancreatic cancer [31,32] and head and neck cancer [33]. Previously, we reported an association between the process of EMT and the expression of several immune checkpoint molecules including PD-L1 in HCC [11,34]. Notably, in HCC patients a close association between EMT and immune checkpoint molecules prognosticated a poor survival [11,34].…”
Section: Introductionmentioning
confidence: 97%
“…We have previously shown that cytokine, tumour necrosis factor (TNF)-α, regulates expression of immune checkpoint molecules in HCC [34]. In this study, we have used another cytokine, transforming growth factor (TGF)-β1, which is a potent inducer of EMT in HCC cells [35][36][37].…”
Section: Introductionmentioning
confidence: 99%